2017
DOI: 10.15809/irriga.2017v22n4p775-788
|View full text |Cite
|
Sign up to set email alerts
|

Cultivars Selection of Carioca Beans Type to Be Harvested in Arid Farmlands

Abstract: CULTIVARS SELECTION OF CARIOCA BEANS TYPE TO BE HARVESTED IN ARID FARMLANDS  SEBASTIÃO SOARES DE OLIVEIRA NETO1; DOUGLAS MARIANI ZEFFA2; MARIA MÁRCIA PEREIRA SARTORI3 E VANIA MODA CIRINO4 1Engenheiro-agrônomo. Doutorando em Agronomia (Agricultura). Departamento de Produção e Melhoramento Vegetal. Faculdade de Ciências Agronômicas (FCA/UNESP - Campus Botucatu), Rua José Barbosa de Barros, 1.780, CEP: 18610-307. Botucatu-SP – Brasil. E-mail: neto.soliver@gmail.com2Engenheiro-agrônomo. Doutorando em Genética e Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…This finding is in agreement with results of Arruda et al [1], Darkwa et al [22], and Mazengo et al [37], who also reported differential responses of common bean genotypes to stressful and non-stressful water regimes. In the literature, although water deficit is considered to be one of the main limiting factors for the common bean, several studies confirmed the wide genetic variability for drought tolerance [38][39][40][41].…”
Section: Discussionmentioning
confidence: 93%
“…This finding is in agreement with results of Arruda et al [1], Darkwa et al [22], and Mazengo et al [37], who also reported differential responses of common bean genotypes to stressful and non-stressful water regimes. In the literature, although water deficit is considered to be one of the main limiting factors for the common bean, several studies confirmed the wide genetic variability for drought tolerance [38][39][40][41].…”
Section: Discussionmentioning
confidence: 93%
“…The magnitude of the damages caused by drought stress depends on the severity, the crop development stage and genotypes' tolerance. The primary damages for common beans are observed in the reproductive stages: flowering and grain filling (Daryanto et al, 2015; Farooq et al, 2016; Oliveira Neto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Drought significantly affects crops' growth and grain yield, causing morphological, physiological, biochemical and molecular alterations in plants (Cui et al, 2019; Du et al, 2020; Todaka et al, 2017). Water deficit severely affects the production of vegetal biomass, modifying the morphological components by decreasing the height, the leaf area, the number of leaves and yield components such as grain number and size, and grain yield (Farooq et al, 2016; Mukeshimana et al, 2014; Oliveira Neto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%